Strategi Pemasaran Digital untuk UMKM dalam Aktivitas Ekspor ke Singapura - Meisyaroh, Siti; Esra, Martha Ayerza; Dasawaty, Elis Sondang (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
This paper explores the benefits of export and import activities for Indonesia, emphasizing the role of digital marketing in maximizing export opportunities. Focusing on Netasia and Okeoce Export Team's initiative, the study employs a problem-solving framework to enhance members' understanding and implementation of digital marketing strategies. Through training, mentoring, and follow-up programs, the initiative aims to empower exporters to tap into the Singaporean market effectively. Positive responses to the training sessions indicate the potential for improved export practices and community welfare through professional organizational management and digital marketing proficiency.